Naked economics undressing the dismal science - Charles J. Wheelan (New York W.W. Norton & Company, 2019)
At last! A new edition of the economics book that won?t put you to sleep. In fact, you won?t be able to put this bestseller down. In our challenging economic climate, this perennial favorite of students and general readers is more than a good read, it?s a necessary investment―with a blessedly sure rate of return. This revised and updated edition includes commentary on hot topics such as automation, trade, income inequality, and America?s rising debt. Ten years after the financial crisis, Naked Economics examines how policymakers managed the worst economic crisis since the Great Depression.
Keywords: Economics